2004
DOI: 10.1590/s0100-879x2004001100005
|View full text |Cite
|
Sign up to set email alerts
|

A functional study of caustic strictures of the esophagus in children

Abstract: The objective of the present study was to assess esophageal motor function in 21 children (7.5 ± 2.9 years) with caustic strictures. Esophageal manometry was performed using a water-infusion system interfaced with a polygraph and displayed on a computer screen. The data were compared with those obtained from 9 healthy children. Radionuclide transit was determined by studying deglutition of a single bolus of 99m Tc pertechnetate in 10 ml of water. Non-peristaltic low-amplitude and long-duration waves were the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In our study, 8% (6/75) of patients had an esophageal fistula, and the incidence was higher in caustic strictures patients (4/6). Caustic esophageal stenosis, with deep and wide esophageal lesions involving the whole esophageal wall, had a greater association with surgery, compared to repeated dilations, which may have low security and high risk of esophageal fistula [23]. The mean length of stenting was 29 days.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 8% (6/75) of patients had an esophageal fistula, and the incidence was higher in caustic strictures patients (4/6). Caustic esophageal stenosis, with deep and wide esophageal lesions involving the whole esophageal wall, had a greater association with surgery, compared to repeated dilations, which may have low security and high risk of esophageal fistula [23]. The mean length of stenting was 29 days.…”
Section: Discussionmentioning
confidence: 99%
“…Da-Costa-Pinto et al (5) suggested that GER is due to both shortening of oesophageal length in the vertical plane because of fibrosis and motility disorder secondary to corrosive substance injury in patients with CES. An objective diagnostic method showing shortening of oesophageal length could not be defined.…”
Section: Discussionmentioning
confidence: 99%
“…An objective diagnostic method showing shortening of oesophageal length could not be defined. In patients experiencing oesophageal replacement and oesophagectomy because of CES, extensive fibrosis is mainly observed in mucosal, submucosal and inner muscular layers in histopathological examinations (5).…”
Section: Discussionmentioning
confidence: 99%
“…In such patients with distal impassable strictures of the thoracic esophagus in addition to a cricopharyngeal stricture, we previously described an inlay pectoralis major myocutaneous flap, which opens access to the cervical esophagus, permitting an esophagocolic anastomosis as a second stage distal to the reconstructed cricopharynx. An anastomosis at this level provides acceptable swallowing ability without aspiration [4].…”
Section: Discussionmentioning
confidence: 99%